2016
DOI: 10.1074/jbc.m116.730564
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Ameliorates Lipotoxicity-induced Glomerular Endothelial Cell Injury by Improving ABC Transporter A1-mediated Cholesterol Efflux in Diabetic apoE Knockout Mice

Abstract: Edited by Dennis VoelkerATP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…Ex-4 and sitaglitin (DPP4 inhibitor) are known to improve kidney function by attenuating inflammation in chronic or diabetic kidney disease models. 17,72 Therefore, it is unclear whether the beneficial effect of Ex-4 is due to its role in improving kidney function, its direct effect on muscle, or both in the current study. Further studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Ex-4 and sitaglitin (DPP4 inhibitor) are known to improve kidney function by attenuating inflammation in chronic or diabetic kidney disease models. 17,72 Therefore, it is unclear whether the beneficial effect of Ex-4 is due to its role in improving kidney function, its direct effect on muscle, or both in the current study. Further studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to the observations in Dex‐treated mice, Ex‐4 significantly increased total muscle mass, CSA of the TA muscle, and muscle function in CKD mice. Ex‐4 and sitaglitin (DPP4 inhibitor) are known to improve kidney function by attenuating inflammation in chronic or diabetic kidney disease models . Therefore, it is unclear whether the beneficial effect of Ex‐4 is due to its role in improving kidney function, its direct effect on muscle, or both in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…The extensive change of pathological procedure contributed to DN, within which leukocyte-EC adhesion and EC inflammation exacerbated glomerular EC injury. [45][46][47][48][49] Hence, reducing leukocyte-EC adhesion and EC inflammation are promising therapeutic tactics to alleviate DN. ICAM-1 is a member of the CAM superfamily and plays an important effect in mediating the migration of leukocytes to pass through the endothelium and enter the kidneys.…”
mentioning
confidence: 99%
“…These effects were accompanied by downregulation of TGFB1 expression, decreased collagen type IV accumulation, suppressed inflammation, reduced apoptosis and lower oxidative stress (Park et al 2007). In alignment with these findings, many other studies also revealed renal beneficial effects of GLP-1 analogues in animal models of diabetic nephropathy suggesting many mechanisms behind these effects such as cAMPprotein kinase A pathway activation, inhibition of renal NAD(P)H oxidases (Hendarto et al 2012, Fujita et al 2014a, downregulation of AGE-induced protein arginine methyltranferase-1 expression (Ojima et al 2013), decreased ICAM-1 production, reduced release of proinflammatory cytokines from macrophages (Kodera et al 2011) and up-regulation of ATP-binding cassette transporter A1 (ABCA1) in glomerular endothelial cells, which promoted cholesterol efflux from cells and blocked inflammatory responses (Yin et al 2016). Moreover, the natriuretic and diuretic effects of GLP-1 analogues and DPP-4 inhibitors through interaction with Na + /H + exchanger isoform 3 could play a role regarding their reno-protective effects.…”
Section: Glp-1mentioning
confidence: 99%